PERANCANGAN MULTIMEDIA INTERAKTIF BERBASIS PENDEKATAN SAINTIFIK PADA PEMBELAJARAN IPS MATERI PETA DAN LETAK GEOGRAFIS INDONESIA KELAS V SEKOLAH DASAR - Ikrimah, Siti Keysa; Marini, Arita; Aruwiyantoko, Anggit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to design an interactive multimedia learning resource based on the scientific approach for Social Studies learning, particularly on map and geographical location materials for fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the 4D development model, limited to the Define and Design stages. The Define stage involved needs analysis, learner analysis, content analysis, task analysis, and the formulation of learning objectives. Data were collected through observations, interviews, and questionnaires administered to teachers and students. The findings revealed that students experienced difficulties in understanding map and geographical location concepts, while the utilization of digital learning media in the classroom remained limited. Based on these findings, the Design stage focused on developing a blueprint for interactive multimedia integrating the scientific approach, including the activities of observing, questioning, collecting information, associating, and communicating. The multimedia was designed as a digital learning resource incorporating text, images, audio, animations, and interactive assessments accessible through electronic devices. The result of this study is a design prototype of interactive multimedia that is expected to serve as an alternative learning medium to support Social Studies learning in elementary schools.